PENERAPAN MANAJEMEN MUTU PENDIDIKAN DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN SISWA DI SD NEGERI TIDUNG - Ilyas, Yudhistira Erwin; Takbir, Muh.; Ramiati, Ramiati (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the implementation of educational quality management in improving student learning effectiveness at SD Negeri Tidung. The urgency of educational quality at the elementary school level underpins this research, given its direct impact on both the learning process and student outcomes. A qualitative descriptive approach was employed, involving principals, teachers, students, and parents as informants. Data were collected through in-depth interviews, classroom observations, and analysis of learning and school evaluation documents. Findings indicate that the principal plays a central role in driving a quality-oriented culture through instructional planning, academic supervision, resource management, and policy reinforcement based on collaborative efforts. Teachers implement structured instructional planning, employ varied media, and engage active learning strategies, although consistency in execution and technology use remain challenges. Quality evaluation is conducted periodically through analysis of learning outcomes and classroom supervision; however, follow-up for continuous improvement is not yet fully structured. The results affirm that adaptive, participatory, and consistent quality management contributes positively to the effectiveness of classroom learning, particularly when leadership, teacher professionalism, and collaborative culture are aligned.